Effects of Aqueous and Methanolic Extracts of Hibiscus rosa-sinensis Leave on the Blood Cells of Mice In vivo - Ghada R.AL-Jarah; Ali S. Mohammed; Hiba A. Jasim (World Journal of Experimental Biosciences, 2017)
Present study focused on in vivo effect of aqueous and methanolic leave extracts of Hibiscus rosa-sinensis plant on different blood cells count of mice that was carried out by using 40 mg / kg of plant extracts orally. Effects of plant extracts were examined after 3 and 7 days of feeding orally. The results showed significant increases (P≤ 0.05) for all parameters (cell types) that were included in current study, total white blood cells (WBCs), lymphocytes, eosinophils, red blood cells (RBCs) and platelets. However, there is no significant difference in Hb values as compared with control.
Keywords: Hibiscus rosa-sinensis, Hb, RBCs, WBCs.